Android-Based Interactive Learning Multimedia to Improve Reading Literacy in High Schools - Faizal; Aunurrahman; Indri Astuti; Herry Sujaini; Urai Salam (Universitas Pendidikan Ganesha, 2024)
Reading is the first skill to master in other literature. Students’ literacy is still low, according to PISA in 2018. There is a need for efforts to improve literacy skills, one of which is the development of literacy platforms. The aim of this research is to develop multimedia learning to improve reading literacy. Research and development (R&D) is based on the Dick & Carey development model. The study was conducted at senior high school, with 30 students participating. Multimedia is validated by material, design, and media experts. Data from the questionnaire instruments and student responses are analyzed with both qualitative and quantitative analysis. Overall, from the data analysis results, expert validation data was declared